Single, very low rituximab doses in healthy volunteers - a pilot and a randomized trial: implications for dosing and biosimilarity testing - Schoergenhofer, Christian (Sci Rep, 2018)
There are no  dose-finding trials available for rituximab that could guide dosing in non-malignant diseases. We hypothesized that currently used doses (≥375 mg/m(2)) exceed several hundred-fold the half-maximal effective dose, which is most sensitive for detecting putative differences between biosimilars and important for dose finding. In an open label, exploratory trial healthy volunteers received single infusions of rituximab at doses of 0.1, 0.3 or 1.0 mg/m(2). Subsequently, in a double-blind, randomized trial healthy volunteers received single infusions of two rituximab products at doses of 0.1 and 0.3 mg/m(2). In the exploratory trial rituximab transiently depleted CD20+ cells by a mean 68% (range: 57–95%), 74% (55–82%) and 97% (94–100%) immediately after the infusion of 0.1 (n = 4), 0.3 (n = 4) and 1 mg/m(2) (n = 8), respectively. In the randomized trial CD20+ cells decreased by a mean 48% (25–84%) − 55% (26–85%) and 81 (67–89%) – 87% (77–96%) after infusion of 0.1 mg/m(2) (n = 12) or 0.3 mg/m(2) (n = 8 proposed biosimilar, n = 4 reference product) of the proposed biosimilar or the reference product, respectively. It is important to understand that in healthy volunteers <1% of the authorized rituximab doses depletes almost all circulating B lymphocytes. Thus, for non-malignant diseases alternative, more cost-effective dosing regimens seem plausible, but require clinical testing. (EudraCT-No. 2010–023781–45; EudraCT-No. 2013–001077–24).